If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x * 3(6 + -2) + 7 = 0 Combine like terms: 6 + -2 = 4 5x * 3(4) + 7 = 0 Reorder the terms for easier multiplication: 5 * 3 * 4x + 7 = 0 Multiply 5 * 3 15 * 4x + 7 = 0 Multiply 15 * 4 60x + 7 = 0 Reorder the terms: 7 + 60x = 0 Solving 7 + 60x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 60x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 60x = 0 + -7 60x = 0 + -7 Combine like terms: 0 + -7 = -7 60x = -7 Divide each side by '60'. x = -0.1166666667 Simplifying x = -0.1166666667
| 4x=5t(3/4) | | 7x+5=7(x+1) | | 12x+72x=21 | | 8x=10t(2/6) | | 9(x+6)+3=57 | | 5*3(6-2)=7 | | 3z-8=4z-4 | | y=67+13 | | 50cos(x/10) | | 2(4k+5)-11k+8+2= | | (a^-6b/ab^5)^-3 | | 6-(2n-7)=4-3n | | 9+2x=3x-7 | | -7x+3=2x+2 | | 11x+3y=56 | | -9(5)+125= | | 15x-28y=32 | | (4x-5y)(16x^2+kxy+25y^2)k= | | 2000-25p=1715+70p | | D^3=125 | | (p^-5/4p^-1)^3 | | -0.444444444=-4/9 | | -0.444444444= | | i^155= | | 7y+5=8y-4 | | 3x^3+3x^2-126x=0 | | 12-1/3x=8 | | 3x^3+3x^2-126=0 | | (2y+4)+(5b+1)= | | ln(x)=ln(x-8)+ln(3) | | 5e^6x=8e^8x | | (9-x)(3x+7)=0 |